2014
DOI: 10.2190/ic.34.2.b
|View full text |Cite
|
Sign up to set email alerts
|

How Partisans Differ from Independents: The Imaginative Functions of Self-Understanding, Rehearsal, and Relationship Maintenance

Abstract: This study looks at partisan voting in light of imagined interactions (IIs). Imagined interactions are a form of daydreaming that allows us to build scripts for use in our interpersonal relationships. II research has generally come from a functionalist perspective, and continues to prove its value in counseling and therapy, as well as to help us to understand intrapersonal communication in general. It has recently been extended into media effects research (i.e., Madison & Porter, 2012, 2014) and with the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Similar concerns emerge with the SII. In this investigations and other investigations using the SII questionnaire, measurement models initially suggest poor fit on common low-performing items, like the reverse-coded items (Bodie et al, 2013;Vickery, Keaton, & Bodie, 2015); those studies reporting reliability estimates also reveal patterns of estimates below conventional thresholds which suggests some item consistency issues (Carpenter, 2016;Honeycutt et al, 1992Honeycutt et al, , 2012Madison et al, 2014). Future research should consider exploring and integrating the 30 years of research and advancement in analytic techniques which have occurred since the initial scale development and factor analyses used to develop the SII (Honeycutt, 2003;Honeycutt et al, 1992Honeycutt et al, -1993.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…Similar concerns emerge with the SII. In this investigations and other investigations using the SII questionnaire, measurement models initially suggest poor fit on common low-performing items, like the reverse-coded items (Bodie et al, 2013;Vickery, Keaton, & Bodie, 2015); those studies reporting reliability estimates also reveal patterns of estimates below conventional thresholds which suggests some item consistency issues (Carpenter, 2016;Honeycutt et al, 1992Honeycutt et al, , 2012Madison et al, 2014). Future research should consider exploring and integrating the 30 years of research and advancement in analytic techniques which have occurred since the initial scale development and factor analyses used to develop the SII (Honeycutt, 2003;Honeycutt et al, 1992Honeycutt et al, -1993.…”
Section: Discussionmentioning
confidence: 51%
“…The primary purpose of this article involves testing and refining the theoretical framework of IIs, but these findings also have important implications in light of the secondary research foci present in II research on extending investigations of IIs into related conversational and relational contexts. First, recognizing recent trends in the intersections of IIs and political communication (Madison et al, 2014;Madison, Honeycutt, Covington, & Auter, in press), these findings suggest the micro-level behaviors and conversations that may relate to political identity and everyday political talk. Recognizing the general topics of talk included in this study such as serious conversation, lecture, and interrogation, these general topics may coincide with specific topics related to political communication: For instance, a serious conversation may involve discussing the formation and beliefs associated with voting; one partner may lecture another on recent news and events occurring in Washington, D.C., or one relational partner may interrogate the other to discuss voting beliefs and behaviors, or even lecture on why certain candidates may be better for local or regional appointments.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Madison et al (2014) examined partisan voting in relation to the functions of IIs. They found that individuals who voted for Republicans and Democrats had less self-understanding and rehearsal IIs than individuals who preferred Independents (Madison et al, 2014) This suggests, explained Madison et al (2014), "that voting along party lines may be a heuristic, or 'mindless' behavior" (p. 105). Warner and Villamil (2017) tested "the depolarizing potential of intrapersonal communication through imagined intergroup political contact" (p. 447).…”
Section: Imagined Interactions In Political Contextsmentioning
confidence: 99%